Philippine medical thesaurus on anatomy in waray - Azura, Leo Christian A., Jr.; Faderon, Rosalie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
The field of medicine is arguably one of the most significant branches of science and technology. There has been increasing funding both from the government and private sector for the past few years. In fact, there are more drugs and health care products available, distributed and used now by the public than it was ten years ago. The quality of life and longevity of humans have dramatically improved in the past few decades; much of it can be attributed to the advancement and improvement of medical techniques.
Yet, despite the improvements, there still exist communication barriers between medical professionals and patients because of the differences of medical knowledge between the patients and doctors. Inevitably, maltreatment occurs, especially in rural areas, because of miscommunication and language barrier between patients and doctors.
Recognizing the problem, the Philippine Multilingual Medical Thesaurus Project was conceived, wherein it intends to translate medical terms taken from the US National Library of Medicine's Medical Subject Headings (MeSH) to various Philippine languages. This study was conducted to translate MeSH terms on Anatomy into Waray as part of the Philippine Medical Thesaurus.
The medical terms were downloaded from the MeSH website. These terms were then translated using the most comprehensive and authoritative dictionaries, after which other translation tools were used to verify and validate the initial translations. Dr. Candelaria Cui Acas, a Waray linguist expert from Komisyon ng Wikang Pilipino ranked the translation tools used for the study. The terms were also listed into translation worksheets by competent respondents consisting of thirteen medical and non-medical professionals. All respondents are native speakers of Waray and reside in Eastern Visayas. Once collection of data was finished, term analysis was conducted using the policies and guidelines on thesaurus construction. After careful examination and verification, the terms were generated and encoded manually. Out of the 2199 medical terms under anatomy [A], 536 terms of 24.37% have suitable Waray equivalent, 14 terms or 0.64% have no equivalent translations but have a scope note, and 1649 terms or 74.99% have neither equivalent translations nor scope notes.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings -- Anatomy -- Philippines; Waray language -- Medical Waray